Teachers Reflective Thinking in Overcoming Student Problems Related to Character Education in Schools - Mastur Thoyib Kesi; Muhammad Iskandar Suhifatullah (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to obtain data and information that can describe the teacher's reflective thinking in overcoming student problems related to character education in schools. This is considered important because there are indications that there are still many teachers who act spontaneously without going through a reflective thinking process in overcoming student problems, even tending to verbal and physical violence. This action is very contrary to the role of the teacher as an educator who should be a model to be imitated by students in schools, especially related to character education. This study uses a descriptive quantitative approach to one variable with a survey technique using a questionnaire in the form of an attitude scale. It is hoped that by obtaining data related to teacher reflective thinking in overcoming student problems, it can be a basis for recommending teacher reflective thinking development programs, so that character education in schools can be improved